An in-vitro morphological study of Q-switched neodymium/YAG laser trabeculotomy. Issue 2 (February 1986) - Venkatesh, S; Lee, W R; Guthrie, S; Cruickshank, F R; Foulds, W S; Quigley, R J; Bailey, R T
Abstract : Laser trabeculotomies produced by directing a pulsed neodymium/YAG laser beam at specimens of human anterior chamber angle obtained post mortem or after enucleation were studied by light microscopy and by scanning and transmission electron microscopy to assess the dimensions of the openings created in the trabecular meshwork, their penetrance to the canal of Schlemm, and the extent or absence of laser induced cellular damage in immediately adjacent tissue. A pulse duration of 40-50 ns at energy levels of around 30 mJ was used and the laser cavity carefully tuned to give a Gaussian spatial mode pattern. Openings in the trabecular meshwork typically of 100 microns in diameter and penetrating through to the canal of Schlemm could be regularly created with only minimal damage to adjacent tissue as judged by transmission electron microscopy. The information so gained may be useful in determining the parameters required for successful laser trabeculotomy as a treatment for primary open-angle glaucoma.